Joint Fronthaul and Multicast Beamforming for Ultra-Dense C-RANs - Tan, Fangqing; Wu, Peiran; Jiang, Ming; Xia, Minghua (2021 IEEE/CIC International Conference on Communications in China (ICCC), 2021)
This work investigates multicast transmission in ultra-dense cloud radio access networks (C-RANs) with wireless fronthaul. To maximize the weighted sum rate (WSR) of multicast services, joint beamforming for fronthaul and access links are designed, subject to the constraints of fronthaul capacity and transmit powers of small base stations and central processor. The formulated optimization problem is however neither smooth nor convex. For ease of mathematical tractability, the smooth and successive convex approximations are exploited to transform the original problem into a sequence of convex problems, and then a first-order algorithm with low computational complexity is developed to find the optimal solution. Numerical results demonstrate that the proposed first-order algorithm can achieve almost the same WSR as that of traditional second-order approaches yet with much lower computational complexity.